2018
DOI: 10.1088/1361-6560/aad47a
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of pediatric 18F-FDG dosimetry: Cristy–Eckerman versus UF/NCI hybrid computational phantoms

Abstract: Because of the concerns associated with radiation exposure at a young age, there is an increased interest in pediatric absorbed dose estimates for imaging agents. Almost all reported pediatric absorbed dose estimates, however, have been determined using adult pharmacokinetic data with radionuclide S values that take into account the anatomical differences between adults and children based upon the older Cristy-Eckerman (C-E) stylized phantoms. In this work, we use pediatric model-derived pharmacokinetics to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(69 reference statements)
1
7
0
Order By: Relevance
“…Dose coefficients for urinary bladder, kidneys, heart, red bone marrow and lungs were estimated by OLINDA 2.0 to be lower than <1Y = patients aged less than one year at scan time 1-5Y = patients aged one year to five years old at scan time 6-10Y = patients aged five years to ten years old at scan time 11-15Y = patients aged eleven to fifteen years old at scan time 16-17Y = patients aged sixteen to seventeen years old at scan time SD = Standard Deviation <1Y = patients aged less than one year at scan time 1-5Y = patients aged one year to five years old at scan time 6-10Y = patients aged five years to ten years old at scan time 11-15Y = patients aged eleven to fifteen years old at scan time 16-17Y = patients aged sixteen to seventeen years old at scan time ICRP 128. Relative differences between ICRP 128 coefficients and those reported in our study are consistent with those demonstrated by Khamwan et al, in which lower lung and urinary bladder dose coefficients were attributed to improved approximation of adjacent organ boundaries as modeled by newer phantoms, compared to older stylized phantoms [32]. As a result of the organ dose differences between the two methods, the ED coefficients also differ, with those estimated by OLINDA 2.0 being approximately 34% less than those provided by ICRP 128.…”
Section: Discussionsupporting
confidence: 92%
“…Dose coefficients for urinary bladder, kidneys, heart, red bone marrow and lungs were estimated by OLINDA 2.0 to be lower than <1Y = patients aged less than one year at scan time 1-5Y = patients aged one year to five years old at scan time 6-10Y = patients aged five years to ten years old at scan time 11-15Y = patients aged eleven to fifteen years old at scan time 16-17Y = patients aged sixteen to seventeen years old at scan time SD = Standard Deviation <1Y = patients aged less than one year at scan time 1-5Y = patients aged one year to five years old at scan time 6-10Y = patients aged five years to ten years old at scan time 11-15Y = patients aged eleven to fifteen years old at scan time 16-17Y = patients aged sixteen to seventeen years old at scan time ICRP 128. Relative differences between ICRP 128 coefficients and those reported in our study are consistent with those demonstrated by Khamwan et al, in which lower lung and urinary bladder dose coefficients were attributed to improved approximation of adjacent organ boundaries as modeled by newer phantoms, compared to older stylized phantoms [32]. As a result of the organ dose differences between the two methods, the ED coefficients also differ, with those estimated by OLINDA 2.0 being approximately 34% less than those provided by ICRP 128.…”
Section: Discussionsupporting
confidence: 92%
“…Paediatric pharmacokinetic data are collected for diagnostic imaging agents, relevant to paediatric studies and the field conversions from older stylized phantoms to more detailed computation hybrid phantoms were created. The effective doses, computed by the UF/NCI hybrid phantom S values, were different than those seen using the C−E stylized phantoms for newborns, 1-year-old and 5 years old, Figures 3 and 4 [6].…”
Section: Paediatric Dose Phantomsmentioning
confidence: 73%
“…RADAR Dose Estimates Report in 2018 based on OLINDA/EXM Version 2.0 for Radiopharmaceutical Dose Estimates [9]. [6].…”
Section: Paediatric Dose Estimations 41 Radar-olinda/exmmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation into the optimal radiotracer activity is critical to pediatric nuclear medicine because children have a higher sensitivity to develop radiation-induced malignancies (1)(2)(3)(4) . A major challenge to radiotracer dosing in pediatrics is the large variation in patient sizespanning an age range from newborn to >18 yrs-old-which impacts dosimetry calculations and image quality measurement techniques (5)(6)(7)(8)(9)(10) . There have been several studies evaluating how the radiotracer dose regimen affects pediatric image quality, and specifically for 18F-Fluorodeoxyglucose (18F-FDG), optimized regimens of 2.0 MBq/kg -5.3 MBq/kg (3 min/bed position) have been reported (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%